A nurse shrub species helps associated herbaceous plants by preventing shade‐induced evaporation in a desert ecosystem. (1st December 2020) - Liu, Liang; Bai, Yuxuan; She, Weiwei; Qiao, Yangui; Qin, Shugao; Zhang, Yuqing
Abstract: Xeric shrubs often play an important role in reversing desertification and promoting ecological restoration of degraded dryland ecosystems. However, how shrubs affect their associated herbaceous species and environmental conditions remains largely unknown. In this study, we conducted a removal experiment along with stable isotope analysis to determine the water use strategy of a shrub species ( Artemisia ordosica ) and its associated perennial graminoids (PG) in the Mu Us Desert, northern China. We observed that in the intact plots, both shrubs and PG predominantly utilized water from the shallow soil layer (0–20 cm, 54.36%, and 63.63%, respectively). Compared to this, when shrubs were removed, soil water content decreased, the main water source of PG switched to the middle soil layer (20–60 cm, 48.25%), and their water use efficiency (WUE) increased. However, the removal of PG had no significant impacts on the soil water content in any layer or on the water source of shrubs but for slightly decreased WUE. We highlighted that rather than hydraulic lift, shade‐induced evaporation decline is the primary mechanism by which shrubs facilitate the growth of associated herbaceous plants in desert ecosystems, indicating that the facilitated herbaceous plants have more flexible water use strategies than shrubs, which probably drives the community succession from being shrub‐dominated to herb‐dominated.